2019
DOI: 10.1093/jas/skz207
|View full text |Cite
|
Sign up to set email alerts
|

Improving accuracy of direct and maternal genetic effects in genomic evaluations using pooled boar semen: a simulation study1

Abstract: Pooling semen of multiple boars is commonly used in swine production systems. Compared with single boar systems, this technique changes family structure creating maternal half-sib families. The aim of this simulation study was to investigate how pooling semen affects the accuracy of estimating direct and maternal effects for individual piglet birth weight, in purebred pigs. Different scenarios of pooling semen were simulated by allowing the same female to mate from 1 to 6 boars, per insemination, whereas litte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…3). Rather high increases in prediction accuracy in honey bees could be expected, since controlled mating in honey bees leaves uncertain relationships, and simulations in other species [39,40] show that uncertain relationships reduce the accuracy of PBLUP EBV more than that of ssGBLUP EBV. Our accuracies for the SDME, i.e.…”
Section: Estimation Of Breeding Valuesmentioning
confidence: 99%
“…3). Rather high increases in prediction accuracy in honey bees could be expected, since controlled mating in honey bees leaves uncertain relationships, and simulations in other species [39,40] show that uncertain relationships reduce the accuracy of PBLUP EBV more than that of ssGBLUP EBV. Our accuracies for the SDME, i.e.…”
Section: Estimation Of Breeding Valuesmentioning
confidence: 99%
“…As in Arango et al (2005b) , censoring models could not be implemented with this dataset since there were no records of in which life stage each animal lost its ear tag. An alternative would be to link animals with missing tags back to the data by using parentage tests based on SNP ( Maiorano et al, 2019 ); however, this would require much cheaper genotyping platforms because the crossbreds are terminal animals.…”
Section: Resultsmentioning
confidence: 99%
“…The increased FS family size always benefits the selection of MGE. Although rarely available within the same generation, maternal half-sibs are naturally more desirable than paternal half-sibs (Maiorano et al 2019) in increasing the accuracy of MGE predictions. In animal breeding studies is often found to be negative (Bradford 1972, Koch 1972, Robinson 1972, Bijma 2006).…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…A general (analytical) method is desirable because the alternative, stochastic simulation, would give answers only to specific situations. Simulation have been used for example by Lourenco et al (2013) to study the effect of genetic evaluation method and Maiorano et al (2019) to study selection when using pooled semen. Where available, maternal half-sibs are expected to be efficient in predicting MGE (Willham 1963, Noble et al 2014, Maiorano et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation